A high-risk airway mycobiome is associated with frequent exacerbation and mortality in COPD. Issue 3 (11th March 2021) - Tiew, Pei Yee; Dicker, Alison J.; Keir, Holly R.; Poh, Mau Ern; Pang, Sze Lei; Mac Aogáin, Micheál; Chua, Branden Qi Yu; Tan, Jiunn Liang; Xu, Huiying; Koh, Mariko Siyue; Tee, Augustine; Abisheganaden, John Arputhan; et al.
Introduction: The chronic obstructive pulmonary disease (COPD) bacteriome associates with disease severity, exacerbations and mortality. While COPD patients are susceptible to fungal sensitisation, the role of the fungal mycobiome remains uncertain. Methods: We report the largest multicentre evaluation of the COPD airway mycobiome to date, including participants from Asia (Singapore and Malaysia) and the UK (Scotland) when stable (n=337) and during exacerbations (n=66) as well as nondiseased (healthy) controls (n=47). Longitudinal mycobiome analysis was performed during and following COPD exacerbations (n=34), and examined in terms of exacerbation frequency, 2-year mortality and occurrence of serum specific IgE (sIgE) against selected fungi. Results: A distinct mycobiome profile is observed in COPD compared with controls as evidenced by increased α-diversity (Shannon index; p<0.001). Significant airway mycobiome differences, including greater interfungal interaction (by co-occurrence), characterise very frequent COPD exacerbators (three or more exacerbations per year) (permutational multivariate ANOVA; adjusted p<0.001). Longitudinal analyses during exacerbations and following treatment with antibiotics and corticosteroids did not reveal any significant change in airway mycobiome profile. Unsupervised clustering resulted in two clinically distinct COPD groups: one with increased symptoms (COPD Assessment Test score) and Saccharomyces dominance, and another with very frequent exacerbations and higher mortality characterised by Aspergillus, Curvularia and Penicillium with a concomitant increase in serum sIgE levels against the same fungi. During acute exacerbations of COPD, lower fungal diversity associates with higher 2-year mortality. Conclusion: The airway mycobiome in COPD is characterised by specific fungal genera associated with exacerbations and increased mortality. The airway mycobiome in COPD is important, and associates with exacerbations, survival and systemic immune responses https://bit.ly/32WA5kJ